2014
DOI: 10.4236/health.2014.614217
|View full text |Cite
|
Sign up to set email alerts
|

Poverty and Eye Health

Abstract: Poverty and eye health, including vision disability from vision impairment and blindness, are believed to be interrelated. The relationship between poverty and eye health can be interpreted as being twofold , in the sense that poverty may be a cause of poor eye health and poor eye health may lead to or deepen poverty. Evidence shows that the burden of vision impairment is high in poor people and vision impairment and poverty are linked to each other. However the empirical evidence to answer the questions-Does … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 45 publications
3
31
1
Order By: Relevance
“…These findings are in affirmation with other research findings conducted in several other countries such as Ethiopia, Kenya, South Africa, Mozambique, Rwanda and Uganda which have shown that many health practitioners lack the necessary skills to adequately respond to the needs of persons with visual impairments [21]. …”
Section: Discussionsupporting
confidence: 87%
“…These findings are in affirmation with other research findings conducted in several other countries such as Ethiopia, Kenya, South Africa, Mozambique, Rwanda and Uganda which have shown that many health practitioners lack the necessary skills to adequately respond to the needs of persons with visual impairments [21]. …”
Section: Discussionsupporting
confidence: 87%
“…1 Low socio-economic status, lack of awareness, and limited access to eye care services increase the risk of blindness. 2 World Health Organization (WHO) has launched the Universal Eye Health Global Action Plan 2014-2019, which aims to reduce avoidable blindness by 25% in 2020. 3 To this end, WHO promotes the assessment of magnitude and causes of visual impairment by implementing eye care services and encourages the development and implementation of integrated national eye health policies.…”
mentioning
confidence: 99%
“…Unlike these countries, people with little resources have limited access to visual health services due to geographical and economic barriers, as well as to barriers related with little knowledge on visual health, in addition to unsatisfactory clinical services (45).…”
Section: Access Barriers To Visual Healthmentioning
confidence: 99%